Noninvasive measurement of time-dependent ultrasound fields in different materials - Chen, Lizhuo; Rupitsch, Stefan; Lerch, Reinhard (IEEE SERVICE CENTER, 445 HOES LANE, PO BOX 1331, PISCATAWAY, NJ 08855-1331 USA, 2012)
For measurements of ultrasound pressure underwater, the light refractive tomography (LRT) is so far the only technique, which is noninvasive, omnidirectional and provides time-resolved results in Pascal. After exploiting all these advantages, LRT shows a great suitability for investigations of ultrasound fields throughout different media. To present the new research possibilities offered by this technique, two novel experiments are demonstrated in the contribution. In the first one, the disturbance induced by a commercial hydrophone to the original sound pressure field is investigated. We utilized LRT to reconstruct the ultrasound pressure field between the transducer and the hydrophone in spatial and temporal dimensions. The results indicate that considerable energy is reflected by the hydrophone tip. Furthermore, we extend the measurement setup and succeed in reconstructing the relative density change induced by ultrasound field within optically transparent Poly(methyl methacrylate) (PMMA).